Pressure-strain loops unveil hemodynamics behind mechanical circulatory support systems. (3rd October 2022) - Landra, F; Mandoli, G E; Sciaccaluga, C; Gallone, G; Pica, A; Cavigli, L; D'Ascenzi, F; Focardi, M; Maccherini, M; Bernazzali, S; Valente, S; Cameli, M
Abstract: Background: Mechanical circulatory support (MCS) systems are increasingly employed in critical hemodynamic states, such as in cardiogenic shock and end-stage heart failure. A thorough understanding of the complex interactions occurring between heart, vasculature and device is essential to optimize patient's management. Purpose: This study aimed to explore the hemodynamic profile of patients under MCS using a non-invasive method based on pressure-strain analysis. Methods: Consecutive patients admitted to the cardiological intensive care unit (CICU) from August 2021 to January 2022 undergoing different MCS systems positioning/implantation were retrospectively reviewed. Patients without a useful echocardiographic exam and/or arterial blood pressure invasive measurement at the time of echocardiography were excluded. Myocardial work analysis by Speckle Tracking Echocardiography (STE) was performed in these patients. Results: 3 patients with intra-aortic balloon pump (IABP), 2 patients with durable left ventricular assist device (dLVAD), 2 patients with temporaneous left ventricle (LV)-to-aortic pump, 1 patient with extracorporeal membrane oxygenation (ECMO) and 1 patient with ECMO and IABP were included. The use of IABP shifted the pressure-strain curve rightward and downward. Global work index (GWI) and global wasted work (GWW) decreased after IABP positioning, whereas global work efficiency (GWE) increased. The use of continuous-flow LV-to-aortic pumps, whether temporaneous or long-term (dLVAD), induced a significant change in the pressure-strain loop, with a shift towards a triangular shape. ECMO positioning alone resulted in a narrowing of the pressure-strain loop, with a decrease in GWI and GWE and an increase in GWW and mean arterial pressure. The combined used of IABP with ECMO widened the pressure-strain loop and improved GWI and GWE. Conclusions: Pressure-strain loops unveil hemodynamic variations induced by mechanical circulatory support systems. Thus, myocardial work could be used to monitor ventricular-arterial-device coupling in such patients and therefore guide tailored management. Funding Acknowledgement: Type of funding sources: None.